2018
DOI: 10.1002/bdr2.1223
|View full text |Cite
|
Sign up to set email alerts
|

Germline but not somatic de novo mutations are common in human congenital diaphragmatic hernia

Abstract: Somatic variants are not common in CDH. To our knowledge, this is the second case of a germline de novo frameshift mutation in NR2F2 in CDH. Since NR2F2 null mice exhibit a diaphragmatic defect, and XIRP2 is implicated in cardiac development, our data suggest the role of these two variants in the etiology of CDH, and possibly cardiac anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Our analysis of the diaphragm revealed multiple somatic variants in the diaphragm’s connective tissue, but none in coding or annotated enhancers, and so these somatic variants are unlikely to be deleterious. A previous study 130 also found no evidence of damaging somatic variants, although this study examined tissue sampled around the periphery of the herniated region and so did not specifically sample the connective tissue that mouse genetic studies predict to be a cellular source of CDH. 17 , 33 , 34 While our study did not find potentially damaging somatic variants in the diaphragm’s connective tissue, we have established an effective discovery strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of the diaphragm revealed multiple somatic variants in the diaphragm’s connective tissue, but none in coding or annotated enhancers, and so these somatic variants are unlikely to be deleterious. A previous study 130 also found no evidence of damaging somatic variants, although this study examined tissue sampled around the periphery of the herniated region and so did not specifically sample the connective tissue that mouse genetic studies predict to be a cellular source of CDH. 17 , 33 , 34 While our study did not find potentially damaging somatic variants in the diaphragm’s connective tissue, we have established an effective discovery strategy.…”
Section: Discussionmentioning
confidence: 99%
“…NR2F2 maps to the 15q26 microdeletion hotspot. NR2F2 is also expressed in the PPF, and a truncating variant in the gene has been identified in two patients with CDH and an atrial septal defect and coarctation/hypoplastic mitral valve, respectively (High et al, 2016;Matsunami et al, 2018). NR2F2 in complex with RERE, Ep300, and an RA receptor promote transcriptional activation of gene targets of RA signaling (Vilhais-Neto et al, 2010).…”
Section: Ra-dependent Gene Expressionmentioning
confidence: 99%
“…In line with this, whole genome sequencing did not find causative somatic variants in diaphragm biopsies (96,97). In contrast, germline de novo variants are often present (33,(96)(97)(98). Females have a higher burden of de novo variants (98), suggesting a female protective model.…”
Section: Cdh Is a Complex Genetic Disordermentioning
confidence: 62%
“…The mutated diaphragmatic cells might not have survived in sufficient quantities and, therefore, be undetectable with sequencing technologies (95). In line with this, whole genome sequencing did not find causative somatic variants in diaphragm biopsies (96,97). In contrast, germline de novo variants are often present (33,(96)(97)(98).…”
Section: Cdh Is a Complex Genetic Disordermentioning
confidence: 73%